Clinical outcomes and aesthetic results of reverse sequence endoscopic versus traditional bilateral nipple-sparing mastectomy with immediate implant-based breast reconstruction-an analysis of initial 116 patients from single institution - Zhang, Qing; Liang, Faqing; Li, Juan; Xie, Yanyan; Feng, Yu; Qiu, Mengxue; Zhou, Jiao; Yang, Huanzuo; Lv, Qing; Du, Zheng-gui (Frontiers in Oncology, 2025)
BackgroundEndoscopic or robotic surgeries can minimize and hide the scars compared to conventional breast reconstruction but are considered unsuitable for bilateral procedures due to the extended operation time. This study explored a novel time-shortening endoscopic technique, namely reverse-sequence endoscopic nipple-sparing mastectomy (R-E-NSM) with bilateral implant-based breast reconstruction (BIBR), and compared it with conventional open surgery in clinical and cosmetic outcomes.MethodsWe retrospectively analyzed patients who underwent BIBR in the West China Hospital from January 2017 to June 2022. Patient characteristics, operation time, postoperative complications, breast satisfaction, and Scar-Q scores were compared between endoscopic and conventional open groups.ResultsAmong 116 patients, 76 underwent R-E-NSM with BIBRs (R-E-BIBR group), and 40 underwent conventional open BIBRs (C-O-BIBR group). The demographics and clinical data were similar primarily (P > 0.05). Compared with the C-O-BIBR group, the R-E-BIBR group had lower rates of total (32.5% versus 6.6%, P < 0.001), major (13.8% versus 2.0%, P < 0.001) and minor (23.8% versus 3.9%, P < 0.001) complications. The operation time between the two groups is not statistically significant (290.2 ± 95.2 mins versus 271.9 ± 95.3 mins, P = 0.327). The Harris scale scored breast satisfaction, and the excellent rate of the C-O-BIBR group was 32.5% while the R-E-BIBR group was 58.0% (P < 0.001). The mean Scar-Q scores were 35.17± 9.6 in the C-O-BIBR group and 81.32 ± 12.3 in the R-E-BIBR group, respectively (P < 0.001).ConclusionThe innovative R-E-NSM with implant-based breast reconstruction makes up for the long operation time of previous endoscopic surgeries and has significant advantages in reducing complication rates and improving the cosmetic results of the postoperative breasts.Level of EvidenceLevel III, Retrospective study.